Evolution of landslide activity, and the origin of debris flows in the El Niño affected Payhua Creek basin, Matucana area, Huarochiri, Peru - Fidel Smoll, Lionel (2006)
Matucana, Perú (population 5800; elevation 2390 m), is located in Andes Occidental, approximately 75 km east of Lima. Matucana shares the Río Rimac (RR) flood plain with a strategic highway and railway. Debris flow-prone Quebrada Payhua (Payhua Creek (QP) joins RR at the upstream end of Matucana. Debris flows from QP dammed the RR and diverted it through Matucana in 1959 and 1983. These large debris flows originated in different parts of the QP basin. The steep ravine systems that produced them are supply-limited with respect to debris flow generation. Based on the volumes of debris flows that were produced by ravine systems in 1983, and channel surveys, a maximum volume of ~250 000 m3 is estimated for the total discharge of a basin-wide debris flow event. Large debris flow events that are conditioned by regional rains are the greatest threat during an El Niño year and in the following year. The area of active landslides near Payhua village, has increased by a factor of five since 1951. Although landslide movement in the recent past has been slow and channel blockage by landslides has not been linked to large destructive debris flows, past events cannot be regarded as confident predictors of future events in this case.